Perception of ergonomic safety training among school teachers in Kelantan, Malaysia - Nurul Husna Che Hassan,; Ahmad Rasdan Ismail,; Noor Adilah Hamzah,; Nor Kamilah Makhtar,; Muhammad Azwadi Sulaiman,; Satrya, Aryana (Penerbit Universiti Kebangsaan Malaysia, 2019)
Ergonomic safety is one of the most important issues in many working sectors and this includes educational institutions especially school. It is important to get the information on the teachers’ perception of ergonomic safety training. Thus, the researcher manages to identify the suitable methods to prevent more ergonomic problem among teachers in future. Aim of this study was to analyze teachers’ perception on ergonomic safety in school and at the same time measured the training requirements on ergonomic safety. Ergonomic safety training in school is important in order to improve good body posture. Survey questionnaires were distributed to 400 teachers. 111 schools randomly selected from the 10 District Education Offices from whole state of Kelantan, Malaysia. Results were then analyzed by using the Statistical Package for the Social Sciences (SPSS) Version 24. Most of the respondents involved in this research are female with the percentage of 68%. Descriptive analysis showed that more than half of respondents understood about ergonomic safety, 78% of them possessed basic safety knowledge and 22% of them lacked on the basic understanding of safety. Interestingly most of the respondents agreed that ergonomic safety should be included in occupational safety and health training in school. It is suggested that all teacher must undergo ergonomic safety training to promote and improve ergonomic safety in school. Higher awareness and more information about ergonomic safety will help teachers teach their students about the importance of ergonomic safety and create a safer environment in their school. As for the conclusion, teachers and students having an important role to ensure ergonomic safety and their commitment will help in reducing the number of ergonomic problems in school.